The Effect of High Dose Methylprednisolone on Experimental Ovarian Torsion/Reperfusion Injury in Rats - Osmanağaoğlu, M. A.; Kesim, M.; Yuluğ, E.; Menteşe, A.; Karahan, C. S. (Geburtshilfe und Frauenheilkunde, 2012)
Purpose: Aim of the study was to evaluate the effects of high dose methylprednisolone on experimental ovarian torsion-detorsion injury in rats. Materials and Methods: Twenty-two Sprague-Dawley rats were randomly divided into three groups. Group 1 (ischemia group, 8 rats) were subjected to left adnexal torsion for 2 h but received no treatment. Group 2 (methylprednisolone group, 8 rats) were subjected to left adnexal torsion for 2 h and received methylprednisolone (30 mg/kg, administered intraperitoneally) at the end of a 2-hour ischemic period followed by 24-hour reperfusion. Group 3 (control group, 6 rats) underwent a sham operation with no adnexal torsion and no treatment. Results: Serum malondialdehyde (MDA), ischemia-modified albumin (IMA), total oxidant status (TOS) and tissue MDA levels were increased in Group 1 rats; total antioxidant status (TAS) levels and oxidative stress index (OSI) were significantly decreased compared with rats in Groups 2 and 3 (p < 0.05). MDA, IMA, TOS and tissue MDA levels were lower and TAS levels and OSI were higher in Group 3 compared to Group 2. Ovarian damage scores in Group 1 were significantly higher compared with Groups 2 and 3 (p < 0.05). Conclusion: This study demonstrated that high dose methylprednisolone reduces ovarian ischemia/reperfusion injury.
Keywords: high dose methylprednisolone; rats; ovarian ischemia-reperfusion; oxidative stres; histopathology